UNPACKING THE COMPLEXITIES OF ECONOMIC SYSTEMS: EXPLORING TRENDS, CHALLENGES AND SOLUTIONS - Dr. Irshad Ahmad Reshi (PT. Radja Intercontinental Publishing, 2025)
Abstract Economic systems are complex networks of interactions and interdependencies that determine the allocation of resources and the distribution of wealth. In recent years, scholars and policymakers have grappled with the challenges posed by the global economic landscape, which has been characterized by increasing inequality, volatility, and uncertainty. This research paper aims to unpack the complexities of economic systems by exploring the trends, challenges, and solutions that have emerged in the field of economics. The paper begins with an overview of the different economic systems that exist and their characteristics. It then analyzes the challenges faced by contemporary economic systems, including inequality, globalization, climate change, and technological disruption. Finally, the paper discusses some of the proposed solutions to these challenges, including social policies, trade agreements, green technologies, and innovation.